Eksplorasi Makanan Khas Tradisional di Kabupaten Enrekang - Ismail Ismail; Mutmainna Muinuddin M. Dyah (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2023)
Many traditions that are spread in the area of ​​Enrekang Regency make it very rich in cultural diversity and traditional specialties. The potential of traditional specialties owned by Enrekang Regency has its own role to attract tourists to come. National identity must be strengthened through the traditional food of Enrekang Regency. As in the case in many countries, which are aggressively and aggressively marketing their food to the world in an effort to strengthen their country. In this study, the object of research is traditional food in Enrekang Regency. Locations of data collection were carried out in all sub-districts in Enrekang Regency. The data sources used were primary data and secondary data. Traditional food producers or traders are the respondents of this research. Data collection techniques are carried out by surveying producers who produce/sell traditional specialties. The data analysis technique of this research is descriptive qualitative. Based on the research results, there are 10 traditional specialties in Enrekang Regency, namely Deppa Te'tekan, Dangke, Pulu Mandoti, Dodol Malino, Deppa Kenari, Nasu Cemba, Baje Kotu, Baje Karrang, Sayur Tuttu and Ayam Bundu-bundu. The main ingredients used in making traditional specialties in Enrekang Regency are mostly from Enrekang Regency itself. Traditional food in Enrekang Regency is processed with various processing and packaging methods that are still fairly traditional.